Explaining the Transnational Design of International Organizations. (17th September 2014) - Tallberg, Jonas; Sommerer, Thomas; Squatrito, Theresa; Jönsson, Christer
Abstract: Past decades have witnessed a shift in international cooperation toward growing involvement of transnational actors (TNAs), such as nongovernmental organizations, multinational corporations, and philanthropic foundations. This article offers a comprehensive theoretical and empirical account of TNA access to IOs. The analysis builds on a novel data set, covering formal TNA access to 298 organizational bodies from fifty IOs over the time period 1950 to 2010. We identify the most profound patterns in TNA access across time, issue areas, policy functions, and world regions, and statistically test competing explanations of the variation in TNA access. The central results are three-fold. First, the empirical data confirm the existence of a far-reaching institutional transformation of IOs over the past sixty years, pervading all issue areas, policy functions, and world regions. Second, variation in TNA access within and across IOs is mainly explained by a combination of three factors: functional demand for the resources of TNAs, domestic democratic standards in the membership of IOs, and state concerns with national sovereignty. Third, existing research suffers from a selection bias that has led it to overestimate the general importance of a new participatory norm in global governance for the openness of IOs.